Pengaruh waktu milling dengan ukuran nano serbuk daun kelor (Moringa oleifera) dan hubunganya dengan bioavailabilitas secara in-vitro dan in-vivo - Syahrial Syahrial; Marni Handayani (AcTion: Aceh Nutrition Journal, 2020)
Calcium deficiency in the body is caused by calcium that has not optimal absorption by the body, resulting in the occurrence of calcium defesiensi. Calcium can not be absorbed maximally by the body when in large molecular form, so the calcium is finally wasted. Therefore, it is necessary to form nano-size so that the calcium can be absorbed by the bones well. The purpose of this research is to see the effect of Milling time with Nano size particles of Kelor powder (Moringa oleifera) and the correlations with Invitro and Invivo bioavailability. The research method is to use the research draft of laboratory experiments, with the sample of the Kelor leaves in powder form, and nanoparticles will be carried out the proximate analysis, nutrient analysis, solubility test, and bioavailability test. The results showed there was a long influence of milling time with nanoparticle size. There is a difference in moisture content, ash, energy, fiber, and total sugar between the leaves of the powder and nano Kelor (p<0,05). There are significant differences in the content of vitamin A, vitamin C, and vitamin K between the form of powder and nano leaf particles (p<0,05). There are significant differences in the levels of calcium, magnesium, phosphorus, potassium, and sodium between the size of the powder to the nano leaf-size particles (p<0,05). The recommendation of consuming nanoparticles kelor flour can be used as a source of food ingredients to increase bone growth and bone density